Flavonoids as key bioactive components of Oxytropis falcata bunge, a traditional anti-inflammatory and analgesic Tibetan medicine. Issue 23 (1st December 2020) - Zhang, Mei-Rong; Jiang, Kan; Yang, Jun-Li; Shi, Yan-Ping
Abstract: The traditional Tibetan medicine Oxytropis falcata Bunge, in the Leguminosae family, is widely used in the west area owing to its significant anti-inflammatory and analgesic activities. O. falcata is rich in flavonoids, which are the main secondary metabolites and key bioactive components of this plant. Up to now, 91 flavonoids have been isolated from O. falcata, including isoflavone, flavone, flavonone, flavonol, homoisoflavonoid, chalcone, dihydrochalcone, chalcone dimers, and pterocarpans. The flavonoids in O. falcata have good anti-inflammatory and analgesic activities, which are comparable to those of a positive drug control (indomethacin). Furthermore, these flavonoids exhibit antibacterial, antioxidant, antitumour, anti-cardiovascular disease, and haemostatic activities. However, to date, O. falcata has not been reviewed comprehensively. Herein, the main secondary metabolites, biosynthetic pathways, and bioactivities of O. falcata are discussed. Graphical Abstract: